Custom Wrench Offers a Break‐Free Method to Close Plastic Valves. Issue 10 (1st October 2015) - Mowbray, Kate
Abstract : A new wrench was developed to close valves where space is limited. Some 3/16‐in. steel flat stock was bent and welded to make the U‐shape handle grip at the back of the wrench to even out the stress points on the valve.